Optimizing Factory Workers Work Shifts Scheduling Using Local Antimagic Vertex Coloring (Contemporary Mathematics, 2024)
Optimization of industrial processes, reduction of worker costs, and protection of workers well-being are significantly dependent on effective work shifts scheduling. This article introduces a new approach to work shifts scheduling by combining Local Antimagic Vertex Coloring. In the provided model, workers are diagrammed as edges, while work shifts are shown as vertices. In order to ensure that adjacent vertices are allocated distinct weights that correspond to non-overlapping work shifts, the Local Antimagic Vertex Coloring approach is used to assign uniform weights to vertices. To optimize the effectiveness of scheduling, regular graphs are used, offering a methodical and fair framework for administrating shift allocations. Adopting this comprehensive approach ensures fair allocation of responsibilities among all workers, minimizes conflicts over shift schedules, and meets operational requirements such as skill levels, shift lengths, and staff availability. By virtue of its versatility, this model may be tailored to various industrial environments, therefore enhancing both scheduling efficiency and staff satisfaction. The actual applications of this method clearly demonstrate its durability, identifying significant improvements in shift planning, reduction of scheduling errors, and a more effective work shifts management process. This paper proposes a comprehensive solution to the complex problem of scheduling work shifts for industrial workers, including both theoretical and practical benefits.
Keywords: work shifts scheduling; workers allocation; local antimagic vertex coloring; scheduling, factory optimization